Developing a Wine Event Portfolio by Wine Stakeholders at Individual Wineries in Victoria, Australia - Paul Strickland (Regional Economic Development Research, 2022)
This exploratory study identifies the economic benefits for wine regions, but specifically where wine stakeholders invest in their own event portfolio creating fun and social occasions. There is little empirical research about the utility of an event portfolio in regional areas and even less in relation to their application to Victorian wine events making the study innovative in nature. It is the first attempt to represent the viewpoint of wine stakeholders. A qualitative geographical bounded case study approach was applied to explore the rational and benefits of developing a wine event portfolio in two Victorian wine regions from a wine stakeholders' perspective. The findings suggest that while destination marketing organizations were familiar with the term 'event portfolio' the concept was quite new for event organizers at individual wineries. Nonetheless, they were planning for multiple events across the year and aimed to capture a range of benefits by holding more than one annual event. These benefits for wine stakeholders' representing individual wineries are an increase in wine sales, diverse demographics of winery visitors and repeat visitation throughout the calendar year. This is despite the increase in financial risk and time commitments by wine stakeholders' hosting wine events at their winery. The paper concludes by suggesting the future research should focus on other viewpoints and replicating this study in other wine regions highlighting the importance and greater benefits of investing in regional development focusing on wine event tourism.